HP(O)Ph2/H2O-promoted hydrodefluorination of trifluoromethyl alkenes. Issue 7 (14th March 2022) - Chu, Xue-Qiang; Sun, Li-Wen; Chen, Yu-Lan; Chen, Jia-Wei; Ying, Xuan; Ma, Mengtao; Shen, Zhi-Liang
Abstract : An efficient transition-metal-free hydrodefluorination reaction of trifluoromethyl alkenes for accessing gem -difluoroalkenes is developed. It was surprising to find that the phosphoryl anion is able to mediate the defluorination. Abstract : An efficient transition-metal-free hydrodefluorination reaction of trifluoromethyl alkenes for accessing gem -difluoroalkenes is developed. It was surprising to find that the phosphoryl anion is able to mediate the defluorination. The successful realization of the reaction could also be attributed to the utility of water as an eco-friendly promoter.